Extreme drought shapes the gut microbiota composition and function of common cranes (Grus grus) wintering in Poyang Lake - Wang, Chaoyang; Zhang, Chao; Cai, Hao; Zhu, Yunlong; Sun, Jiwan; Liu, Wen; Wang, Zhenyu; Li, Yankuo (Frontiers in Microbiology, 2024)
IntroductionExtreme weather events driven by climate change profoundly affect migratory birds by altering their habitats, food sources, and migration routes. While gut microbiota is believed to play a role in helping birds adapt to environmental changes, research on how extreme weather impacts their gut microbiota and how these microbial communities respond to such conditions has been limited.Methods16S rRNA gene sequencing was utilized to investigate the gut microbiota of common cranes (Grus grus) wintering at Poyang Lake from 2020 to 2023, with a particular focus on their response to extreme drought conditions on both inter-annual and monthly timescales.ResultsThe results revealed that extreme drought conditions substantially impact gut microbiota, with inter-annual water-level fluctuations exerting a more pronounced impact on microbial community structure than that of inter-monthly fluctuations. Notably, a significant decline in bacterial diversity within the gut microbiota of common cranes was observed in the extreme drought year of 2022 compared with other years. Monthly observations indicated a gradual increase in gut microbial diversity, coinciding with relatively minor water-level changes. Key taxa that responded to drought included the Enterobacteriaceae family and Bifidobacterium and Lactobacillus species. Additionally, functional genes related to carbohydrate metabolism, the phosphotransferase system, and the two-component systems were significantly enriched during the extreme drought year. These functions may represent adaptive mechanisms by which the gut microbiota of common cranes respond to drought stress.DiscussionThis research provides novel insights into the temporal variability of gut microbiota in wintering waterbirds, underscoring the significant impact of climatic fluctuations on microbial communities. The findings highlight the importance of understanding the ecological and functional responses of gut microbiota to extreme weather events, which is crucial for the conservation and management of migratory bird populations in the face of climate change.